The Role of Training, Certification, and Employee Education in Improving Employee Performance - Putra, Andri Nusantara; Sriyono; Setiyono, Wisnu Panggah (Jurnal Manajemen, 2025)
Training, certification, and education play a crucial role in improving employee performance at the Asam-Asam Power Plant (PLTU Asam-Asam), as these three aspects enhance the competencies, skills, and knowledge required to address the company's operational challenges. The study aims to determine the influence of training, certification, and education on improving employee performance at PLTU Asam-Asam. This research employs a quantitative method with a hypothesis testing design to examine the causal relationship between the variables of Training, Certification, Education, and Employee Performance at PLTU Asam-Asam. It uses saturated sampling techniques and data analysis through SEM-PLS to test the validity, reliability, and influence among variables. The analysis shows that training has the highest influence, with a beta coefficient of 0.396 and a t-statistic value of 4.588, followed by certification with a beta coefficient of 0.240 and a t-statistic value of 2.482, and education with a beta coefficient of 0.233 and a t-statistic value of 2.543. These human resource development programs are deemed effective, with respondents' average perceptions of the training, certification, and education variables at 4.47, 4.46, and 4.48, respectively, on a Likert scale. The study also notes that the model's Goodness of Fit value of 0.583 indicates a good model fit, while the Q² predictive relevance value of 0.466 demonstrates the model's predictive capability in explaining the influence of independent variables on employee performance.